(untitled) (Progressive Agriculture, 2017)
The study was conducted to investigate the impacts of Brahmaputra riverbank erosion hazard on livelihood pattern of char people, agriculture and environment. Five villages of Mymensingh district near to the Brahmaputra River were selected. A semi-structured questionnaire, interview, secondary data sources, field observation and focus group discussion were utilized for this study. Result revealed that erosion has a great impact on livelihood, agriculture, environment and other sectors. Population displacement is a common phenomenon in the study area due to riverbank erosion. During the river erosion 73% people took temporary and 27% took permanent migration where 26% had chosen town as permanent migration. About 56% people loss 0 to 5 acres and 33% loss 6 to 10 acres of their land. Before riverbank erosion 61% people were involved in farming but after riverbank erosion it decreased into 24%. About 88% respondents used tube well as the main source of drinking water, which was smaller than that of the national rural rate 96.42% and some people used river water as drinking, bathing, washing clothes and household materials, and that was so unhygienic. The major diseases like diarrhea, dysentery, asthma, TB, typhoid, etc. were prevalence during flood and river erosion as well as medical facility was also poor. Only 9% people used medicine from consultant doctor. The study has explored a negative fact that without any organizational support, the people of the villages have to formulate and undertake various adaptation techniques in their own way. Finally, the study has recommended some suggestions for the policy planners and implementers for the future development of the riverbank erosion victims in Bangladesh. It emphasizes the importance of the government and non-governmental organizations to take their own responsibility to the devastating situation of the riverbank erosion. Progressive Agriculture 28 (2): 73-83, 2017